Model Matematika Optimasi untuk Perbaikan Proses Penggorengan Vakum Terhadap Tekstur Keripik Buah - J Jamaluddin; Budi Rahardjo; Pudji Hastuti; R Rochmadi (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
Hard and crunchy are specific characteristics of fried product prefered by consumer. To have texture of crunchy product being suitable with consumer taste, it is necessary to observ characteristic change of raw material and frying condition. In frying process, the changes of hardness and crunchiness characteristics of food occur. These changes are predicted caused by free water vaporization and the decrease of starch content in food. The objective of this research is to develop mathematical model of hardness and crunchiness changes as the function of water and extract content degradation. Sample of the research is jack fruit fried in the temperature of 70–100° C, duration of 15–60 minutes, and pressure of 80–90 kPa. The parameters observed are hardness and crunchiness, water and starch content before and after frying. The result showed that hardness and crunciness change as the function of water vaporization and the decrease of starch content can be used to predict hardness and crunciness of product during vacuum frying.